Genotype-phenotype correlations and clinical outcomes of genetic TRPC6 podocytopathies - McAnallen, Susan; Elhassan, Elhussein A E; Stoneman, Sinead; Pinto e Vairo, Filippo; Hogan, Marie C; Hoefele, Julia; Clince, Michelle; Mekraksakit, Poemlarp; Titan, Silvia M; Jorge, Sofia; Calado, Joaquim; Decramer, Stéphane; et al. (Nephrology, dialysis, transplantation, 2025)
Podocytopathy associated with likely pathogenic/pathogenic variants of Transient receptor potential cation channel subfamily C member 6 (TRPC6) (TRPC6-AP) has been recognized for about 20 years. As a result of its rarity however, the spectrum of clinical phenotypes and genotype-phenotype correlation of TRPC6-AP remains poorly understood. Here, we characterized clinical, histological and genetic correlates of familial and sporadic patients with TRPC6-AP.In this multicentre observational study, an online questionnaire followed by a systematic literature review was performed to create a cohort with comprehensive data on genetic and clinical outcomes [age of onset, clinical presentation, treatment response, kidney biopsy findings and progression to kidney failure (KF)]. Logistic regression, Cox proportional hazards model and Kaplan-Meier analyses investigated the associations between genetic variants and disease progression.Among 87 families (96 familial and 45 sporadic cases), 31 distinct missense TRPC6 variants (including 2 novel) were identified, with c.2683C>T p.(Arg895Cys) and c.523C>T p.(Arg175Trp) the commonest variants. Proteinuric kidney disease/nephrotic syndrome was the most common clinical presentation (83.7%), while focal segmental glomerulosclerosis was the most common histological finding (89.4%). By 33 (interquartile range 17-40) years, 48.9% (69/141) of patients had progressed to KF. Sporadic TRPC6-AP demonstrated an earlier progression to KF than familial cases (P = .001) and were more likely to present with nephrotic syndrome [odds ratio 4.34 (1.85-10.15); P = .001]. Gain-of-function TRPC6 variants were more frequent in familial than sporadic TRPC6-AP (70.8% vs 44.4%; P = .004). Compared with patients with other TRPC6 variants, patients with TRPC6 p.R175W and p.R895C variants progressed to KF earlier [median kidney survival of 21 years, hazard ratio 2.985 (95% confidence interval 1.40-5.79); and 38 years, hazard ratio 1.65 (95% confidence interval 1.01-2.81), respectively, log-rank P = .005].Our study shows unique clinical and genetic correlations of TRPC6-AP, which may enable personalized care and promising novel therapies.
Vorab veröffentlicht: 19. Mai 2025
Gesehen am 29.10.2025